(untitled) (Applied Biological Research, 2013)
The present paper describes an improved method for the detection of pebrine (Nosema bombycis) spores using powdered formulation of Ambistryn-S (antibiotic preparation of streptomycin sulphate) and Transco Trichostar (a biofungicidal preparation of Trichoderma viridae) to the larval, pupal and moth suspension after oviposition to check other bacterial and fungal growth. Alternate refrigeration used in this method simultaneously induces the pathogen to complete its intermediate life cycle stages and triggers production of maximum number of Nosema spores having long polar tubes (LT) with highly developed coat wall protein that facilitate the observation of pathogen under light microscope. This low-cost method performed successfully in detecting the pebrine spores at very low intensity in small populations, involved minimum skill and gave very quick results.